Konformitas dan Fanatisme Remaja Kepada Korean Wave (Studi Kasus pada Komunitas Penggemar Grup Musik CN Blue) - Widarti W (Universitas Bina Sarana Informatika, 2016)
Korean wave fever became one of the phenomena of conformity. In Indonesia, especially Jakarta, many teenagers hypnotized by all cultures derived from the ginseng country. Invasion of South Korean culture worldwide including to Indonesia gives tone and brings its own implications for fans of Korean cultural products especially Korean drama music. Even to imitate the style of Korean artists. This study aims to determine how conformity korean wave aplied and occurs, especially for fans of Korean music and Korean drama group. This research use traditional methods of qualitative descriptive approach. The subject is adolescent in the age category 16 to 28 years old. The results of this study showed that the subjects pay homage enthusiasm and love for music groups and artists as well as the Korean drama fanatics behave as culture originating from the country.Keyword: Konformitas, Fanatisme, Korean Wave